Strategies to Stimulate Mobilization and Homing of Endogenous Stem and Progenitor Cells for Bone Tissue Repair - Herrmann, Marietta; Verrier, Sophie; Alini, Mauro (Frontiers in Bioengineering and Biotechnology, 2015)
The gold standard for the treatment of critical sized bone defects is autologous or allogenic bone graft. This has several limitations including donor site morbidity and the restricted supply of graft material. Cell-based tissue engineering strategies represent an alternative approach. Mesenchymal stem cells (MSCs) have been considered as a source of osteoprogenitor cells. More recently, focus has been placed on the use of endothelial progenitor cells (EPCs), since vascularization is a critical step in bone healing. Although many of these approaches have demonstrated effectiveness for bone regeneration, cell-based therapies require time consuming and cost expensive in vitro cell expansion procedures. Accordingly, research is becoming increasingly focused on the homing and stimulation of native cells. The stromal cell-derived factor 1 (SDF-1) – CXCR4 axis has been shown to be critical for the recruitment of MSCs and EPCs. Vascular endothelial growth factor (VEGF) is a key factor in angiogenesis and has been targeted in many studies. Here, we present an overview of the different approaches for delivering homing factors to the defect site by absorption or incorporation to biomaterials, gene therapy or via genetically manipulated cells. We further review strategies focusing on the stimulation of endogenous cells to support bone repair. Finally, we discuss the major challenges in the treatment of critical size bone defects and fracture non-unions.